MineralBay – the portal for raw materials and projects from subsurface construction / MineralBay – das Portal für mineralische Rohstoffe und Projekte aus dem Untertagebau. Issue 4 (3rd August 2015) - Erben, Hartmut; Galler, Robert; Grechenig, Thomas
Abstract In order to achieve higher utilisation rates for the material excavated from underground construction sites, one of the main objectives is efficient, digital processing of available data on material, mass and time parameters for the mined rock. Selected information needs to be made available to a wide audience at the same time. This initiates a value chain, which goes far beyond the construction industry and enables successful upcycling. The evolving software MineralBay is committed to this goal by using the internet to bring together owners or suppliers of mineral resources with customers easily, quickly and at any time to facilitate the exchange and trading of raw materials. MineralBay is a management and merchandising system for excavated material, whose speciality is access to and processing of real‐time data, e.g. in the form of online material analysis results from tunnel boring machines. The information obtained is used for quality management of already placed excavation material and for gapless documentation of the material flow from the beginning to the end of the construction project. Eines der Kernziele zum Erreichen höherer Verwertungsquoten von Ausbruchmaterial bei untertägigen Bauprozessen ist die effiziente digitale Aufbereitung vorhandener Daten zu Material‐, Massen‐ und Zeitparametern des Tunnelausbruchs, wobei zugleich ausgewählte Informationen einem breiten Interessentenkreis zugänglich sein sollen. Dadurch wird eine Wertschöpfungskette initialisiert, die weit über die Baubranche hinausgeht und so ein erfolgreiches Upcycling ermöglicht. Diesem Ziel soll die in Entwicklung befindliche Software MineralBay dienen, die Besitzer, Lieferanten und Bedarfsträger mineralischer Rohstoffe einfach, schnell und zu jeder Zeit über das Internet zusammenführen kann, um so den Austausch und Handel von Rohmaterialien zu vereinfachen. MineralBay ist ein Ausbruchmaterialverwaltungs‐ und ‐vermarktungssystem, dessen Besonderheit die Anbindung an Echtzeit‐Datenanalysen ist, z.B. in Form einer Online‐Materialanalyse auf der Tunnelbohrmaschine. Die dadurch gewonnenen Informationen dienen dem Qualitätsmanagement des vermittelten Ausbruchmaterials und der lückenlosen Dokumentation des Materialstroms vom Beginn bis zum Ende des Bauprojekts.